Chemical vapour deposition of antimony chalcogenides with positional and orientational control: precursor design and substrate selectivity. Issue 2 (21st November 2014) - Benjamin, S. L.; de Groot, C. H.; Hector, A. L.; Huang, R.; Koukharenko, E.; Levason, W.; Reid, G.
Abstract : A series of alkylchalcogenostibines have been synthesised and employed as precursors for the chemical vapour deposition of Sb2 Te3 and Sb2 Se3 . Variations in substrate and temperature give different film morphologies, and patterned arrays can be deposited using substrate selectivity. Abstract : A series of alkylchalcogenostibines, Me2 SbSe n Bu, MeSb(Se n Bu)2, Sb(Se n Bu)3 and MeSb(Te n Bu)2, have been designed and synthesised as potential precursors for chemical vapour deposition (CVD) by reaction of n BuELi (E = Se, Te) with the appropriate halostibine, Me3− n SbCl n ( n = 1, 2, 3), and characterised by 1 H, 13 C{ 1 H} and 77 Se{ 1 H} or 125 Te{ 1 H} NMR spectroscopy as appropriate. MeSb(Se n Bu)2 and MeSb(Te n Bu)2 are very effective single source precursors for the low pressure CVD of high quality crystalline thin films of Sb2 Se3 and Sb2 Te3, respectively, confirmed by scanning electron microscopy, energy dispersive X-ray spectroscopy, Raman spectroscopy and thin film X-ray diffraction. Hall conductivity, carrier mobility, carrier density and, in the case of Sb2 Te3, Seebeck coefficient measurements reveal electronic characteristics comparable with Sb2 E3 deposited by atomic layer deposition or molecular beam epitaxy, suggesting materials quality and performance suitable for incorporation into electronic device structures. Choice of substrate and deposition conditions were found to significantly affect the morphology and preferred orientation of Sb2 Te3 crystallites, enabling deposition of films with either 〈1 1 0〉 or 〈0 0 1〉 alignment. Use of micro-patterned substrates allowed selective deposition of crystalline 2D micro-arrays of Sb2 Te3 onto exposed TiN surfaces only.